Cutwornn that damage summer crops and pastures of alfalfa in the oriental region of the province of La Pampa. Bibliographical review (Semiárida, 2020)
The cutworms complex in the semiarid oriental region of La Pampa province is integrated for: Agrotis malefida, A. gypaetina, Peridroma saucia y Pseudoleucania bilitura (Lepidoptera: Noctuidae). The present contribution is a synthesis of the available information on these four species that cause damages in the cultures. The group of the noctuidos is described and the biology is synthesized with special reference to the species mentioned previously. Also, for each one of the species it is provided the geographical distribution and a listing of host plants. The complex includes three neotropicales species (A. malefida, A. gypaetina and Pseudoleucania bilitura); the distribution of the first one extends until the South of Neártida and a cosmopolitan species (Peridroma saucia). The information is emphasized taken place on the group in Argentina.
Keywords: cutworms; Noctuidae; geographic distribution; host plants; Argentina; review